DIMINUTIVE REFERENCES IN PERSONAL NAMES AMONG ABAKALIKI PEOPLE OF EBONYI - Ozo, Glory Onyome; EMEKA-NWOBIA, Ngozi U.; Obinna, Nancy Ngozi (EBSU Journal of Social Sciences and Humanities, 2025)
Personal names are identity labels for both the individuals bearing them and their cultural societies. This study is aimed at exploring the etymologies of the nwa names among the Abakaliki people of Ebonyi State, with a view to determining their meaningfulness or opacity. Data are drawn from observation, oral interviews with forty (40) learned and culturally informed participants, and library and internet secondary sources. Content analysis and systematic review are deployed in the analysis of the gathered data. The study leans on JS Mill’s theory of Connotation vs. Denotation Distinction (CDD) to argue and show that personal names, including the nwa names among the Abakaliki people, have both connotative and denotative meanings and references amidst complexity. The analysis proves the meaningfulness of the nwa names on cultural and pragmatic grounds and thereby shows that the names are not diminutive as erroneously or narrowly perceived by many. The study concludes that the references to various non-human entities are what make many people in contemporary times to consider most African indigenous names as being diminutive, but they are actually not. The study calls on Africans to uphold and promote their indigenous systems and identities, such as the nwa names among the Abakaliki people, across generations regardless of the sustained contact with the West and the emergent trends of globalisation.